ANALISIS STRATEGI PENINGKATAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DALAM UPAYA OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN INDRAMAYU - Rachma Aulia Putri Kurniawan; Muhammad Dahlan (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
This study analyzes how the strategy to increase Motor Vehicle Tax (PKB) revenue in P3DW Indramayu 1 in an effort to optimize Regional Original Income (PAD) in Indramayu Regency with a qualitative approach and descriptive analysis and using data collection techniques in the form of interviews, observations, and documentation. This research is motivated by Motor Vehicle Tax which is one of the largest sources of Regional Original Income in Indramayu Regency. The results of the study indicate that there are factors that influence the implementation of the strategy, namely regulations, human resources, facilities and infrastructure, raw material stocks, and taxpayer expectations. The strategy to be implemented is to expand collaboration with Bapenda Indramayu in response to the implementation of the Opsen PKB policy, improve facilities and infrastructure, provide creative services by carrying the tagline "Paling Ayu Bersatu", offer alternative payment methods, and utilize local event moments to collect. The results of the analysis of the success of the strategy indicate that the strategy used was unsuccessful in increasing PKB as seen from the decrease in the target and realization of PKB per July 2025 from the previous year. This decline was not only due to the less than optimal implementation of the strategy, but also influenced by the introduction of new regulations, namely the HKPD Law. However, the implemented strategy was still successful in creating satisfaction and convenience for taxpayers.